Exploring the Role of a Strength Training Facility on Community Development: Cree Nation of Chisasibi - Randall, Andrew (Université d'Ottawa / University of Ottawa, 2016)
Community development (CD) is viewed as a way to improve the social, physical, organizational and economic outcomes of a community. The purpose of this study was to explore the role of a strength training facility on CD and provide an insight into its impact on the community. Qualitative research was conducted by two data collection exercises. The first was a 12-week period, while the second was one week long. A segmented thematic analysis was used to explore the data provided by three target groups and participants’ observations. The findings provided insight into the facility’s contribution to CD in particular, noting that a strength training facility can influence personal, economic, social, environmental and organizational outcomes within a community. The research contributes to the existing literature in leisure by providing evidence of CD from a remote First Nations community. The research reveals how arrangements for physical activities can improve the welfare of a community.
Keywords: community development; Chisasibi; strength training facility; community leisure initiative model; First Nations; recreation and leisure